Dual inhibition of AKT‐mTOR and AR signaling by targeting HDAC3 in PTEN‐ or SPOP‐mutated prostate cancer. Issue 4 (9th March 2018) - Yan, Yuqian; An, Jian; Yang, Yinhui; Wu, Di; Bai, Yang; Cao, William; Ma, Linlin; Chen, Junhui; Yu, Zhendong; He, Yundong; Jin, Xin; Pan, Yunqian; et al.
Abstract: AKT‐mTOR and androgen receptor (AR) signaling pathways are aberrantly activated in prostate cancer due to frequent PTEN deletions or SPOP mutations. A clinical barrier is that targeting one of them often activates the other. Here, we demonstrate that HDAC3 augments AKT phosphorylation in prostate cancer cells and its overexpression correlates with AKT phosphorylation in patient samples. HDAC3 facilitates lysine‐63‐chain polyubiquitination and phosphorylation of AKT, and this effect is mediated by AKT deacetylation at lysine 14 and 20 residues and HDAC3 interaction with the scaffold protein APPL1. Conditional homozygous deletion of Hdac3 suppresses prostate tumorigenesis and progression by concomitant blockade of AKT and AR signaling in the Pten knockout mouse model. Pharmacological inhibition of HDAC3 using a selective HDAC3 inhibitor RGFP966 inhibits growth of both PTEN‐deficient and SPOP‐mutated prostate cancer cells in culture, patient‐derived organoids and xenografts in mice. Our study identifies HDAC3 as a common upstream activator of AKT and AR signaling and reveals that dual inhibition of AKT and AR pathways is achievable by single‐agent targeting of HDAC3 in prostate cancer. Synopsis: Both AKT and AR signaling pathways are activated in PTEN‐deficient or SPOP‐mutated prostate cancers and inhibition of one pathway often activates the other. AKT and AR pathways in PTEN‐deficient or SPOP‐mutated prostate cancers are both inhibited by the same HDAC3 inhibitor RGFP966. HDAC3 is the only member of the class I/II HDAC family that regulates AKT phosphorylation and its expression correlates with AKT phosphorylation in prostate cancer patient specimens. HDAC3 regulation of AKT phosphorylation is mediated by deacetylation of K14 and K20 residues on AKT and the function of HDAC3 in the cytoplasm. Conditional knockout of Hdac3 gene blocks Pten deletion‐induced Akt activation, prostate tumorigenesis and progression, and overall survival of mice. The selective HDAC3 inhibitor RGFP966 inhibits growth of both PTEN‐deficient and SPOP‐mutated prostate cancer cells by suppressing phosphorylation of AKT and its downstream effector kinases and AR expression. Abstract : Both AKT and AR signaling pathways are activated in PTEN‐deficient or SPOP‐mutated prostate cancers and inhibition of one pathway often activates the other. AKT and AR pathways in PTEN‐deficient or SPOP‐mutated prostate cancers are both inhibited by the same HDAC3 inhibitor RGFP966.